Photoluminescence investigation of the indirect band gap and shallow impurities in icosahedral B[subscript]12As[subscript]2 - Klein, P. B.; Nwagwu, Ugochukwu; Edgar, James H.; Freitas, J. A., Jr. (My University, 2012)
The indirect band gap of icosahedral B[subscript]12As[subscript]2 (IBA) has been determined by variable temperature photoluminescence measurements (8 K-294 K) on solution-grown bulk samples. In addition, evidence of three shallow acceptor levels and one shallow donor level is reported. The low-temperature spectra were characterized by broad and intense deep defect emission, donor-acceptor pair (DAP) bands, and exciton recombination. The appearance of DAP emission verifies the incorporation of a donor in IBA, which has not been reported previously. The temperature dependence of the free exciton (FE) intensity reflected a FE binding energy of 45 meV. The variation of the FE peak position with temperature was fitted with both Varshni and Pässler models to determine an expression for the temperature dependence of the indirect band gap. The resulting low and room temperature band gaps are E[subscript]g(0) = 3.470 eV and E[subscript]g(294 K) = 3.373 eV, respectively. The latter is not consistent with previous reports of the room temperature band gap, 3.20 eV and 3.47 eV, derived from band structure calculations and optical absorption, respectively. The origin of these discrepancies is discussed. The DAP spectra reveal three relatively shallow acceptors with binding energies of ≈175, 255, and 291 meV, and a shallow donor with binding energy ≈25 meV. Although the identity of the individual acceptors is not known, they appear to be associated with the light-hole band. The small donor binding energy is suggestive of an interstitial donor impurity, which is suspected to be Ni.
Keywords: Photoluminescence; Icosahedral B12As2; Indirect band gap